COMPLEMENTARY ENTROPY AND WAVELET ANALYSIS OF DRILLING-ABILITY DATA - Frantziskonis G.; Denis A. (My University, 2003)
The paper combines wavelet and entropy analysis of nonstationary drilling-ability data in order to obtain optimum information on the mechanical behavior of different geological formations. Both methods are multiscale in nature, and while entropy analysis provides information on stationary subdomains, wavelet analysis identifies dominant scales or range of scales at which the entropy analysis is most useful. The combination of the techniques yields relatively simple results that can aid the drilling process by providing information on delays to be expected.
Keywords: MULTISCALE; NON-STATIONARY; SPATIAL SERIES; TUNNELLING